Review. Functional glasses and glass-ceramics derived from iron rich waste and combination of industrial residues - Chinnam, Rama Krishna Satish; Francis, A. A.; Will, Julia; Bernardo, Enrico; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2013)
Wastes from industrial processes and energy generation facilities pose environmental and health issues. Diversion of waste from landfill to favour reuse or recycling options and towards the fabrication of marketable products is of high economic and ecologic interest. Moreover safe recycling of industrial wastes is necessary and even vital to our society because of the increasing volume being generated. Glasses and glass-ceramics attract particular interest in waste recycling concepts. Novel and/or improved glass-based products from wastes should meet a variety of demands, among which the functional requirements are paramount. The investigations reviewed in this paper focusing on iron rich waste materials demonstrate the potential of turning these silicate based wastes into functional glass-based products. By properly selecting iron oxide containing residues and processing parameters, functional glass-based products with suitable catalytic activity, magnetic, optical and electrical properties can be obtained. The possibility of fabricating highly porous materials using different types of wastes for sound and thermal insulating as well as catalytic support applications is also discussed based on literature results. Thus, porosity can be considered to achieve particular properties in waste derived products. © 2012 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.review
Keywords: Functional properties; Glass-ceramics; Porous materials; Silicate waste